Efficient design of experiment for exponential regression models - Holger Dette; Ignacio Martinez Lopez; Isabel M. Ortiz Rodriguez; Andrey Pepelyshev (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
In this paper robust and efficient designs are derived for several exponential decay models. These models are widely used in chemistry, pharmacokinetics or microbiology. We propose a maximin approach, which determines the optimal design such that a minimum of the D-efficiencies (taken over a certain range for the nonlinear parameters) becomes maximal. Analytic solutions are derived if optimization is performed in the class of minimal supported designs. In general the optimal designs with respect to the maximin criterion have to be determined numerically and some properties of these designs are also studied.
Keywords: 519; exponential regression model; D-optimal design; robust design; maximin design; pharmacokinetics; microbiology; Regression; Test; Theorie